Efficacy and Safety of the Reduced Bivalirudin in Patients Undergoing Coronary Angiography or Percutaneous Coronary Intervention Stratified by Renal Function (REDUCE BOLUS): A Single-Blind, Stratified Randomized, Non-inferiority Trial - Hu, Qiang; Han, Ya-Ling; Zhou, Tie-Nan; Wang, Xiao-Zeng; Zhang, Quan-Yu (Frontiers in Cardiovascular Medicine, 2022)
Background: In clinical practice, some cases indicate that the loading dose of bivalirudin may increase the bleeding risk, particularly in patients with renal insufficiency. Therefore, this study aimed to assess the efficacy and safety of the low dose (80%) bolus injection of bivalirudin in patients with coronary angiography or PCI stratified by renal function. Methods: 204 individuals in REDUCE BOLUS trial were prospectively stratified 1:1 to estimated glomerular filtration rate (eGFR) ≥60ml/min cohort or eGFR<60ml/min cohort, then randomized 1:1 to reduced bolus bivalirudin group (i.e., the experimental group) or normal bolus bivalirudin group (i.e., the control group) respectively, followed by the maintenance dose of bivalirudin during the operation. The primary endpoint was to compare the differences of the area under the curve of activated clotting time (ACT) between the two groups. The secondary endpoints were the postoperative net adverse clinical events (NACE) before discharge, defined as the all-cause mortality, recurrent myocardial infarction, ischemia-driven target vessel revascularization, stroke, and bleeding events. Safety endpoints included bleeding events and stent thrombosis after the operation. Results: Between January 3, 2020, and March 26, 2021, 204 patients undergoing coronary angiography were randomly assigned, including 102 (51 in the control group and 51 in the experimental group) with normal eGFR and 102 (51 control and 51 experimental) with abnormal eGFR. No difference was observed in the curve of ACT between the control group and the experimental group (0.55±0.09 vs.0.56±0.08, P=0.542 and 0.55±0.06 vs. 0.57±0.05, P=0.075, respectively for normal eGFR cohort and abnormal eGFR cohort). The one-sided 97.5% lower confidence bound for the difference in the area under the ACT curve was -0.017 and 0.0015 in eGFR≥60 ml/min and eGFR<60 ml/min cohort, respectively, both above the preset non-inferiority criterion of -0.07, establishing the non-inferiority. There was no postoperative net adverse event and stent thrombosis before discharge in each group. Conclusion: In patients undergoing cardiac catheterization, the efficacy and safety of the reduced bolus of bivalirudin were non-inferior to the normal one, even in patients with chronic kidney disease. Trial registration: This trial was registered with Clinicaltrials.gov as identifier NCT03588611.